Crisis and Hope among the World’s Urban Poor: Religion responds to Covid-19 - Grace R. Dyrness (International Journal of Interreligious and Intercultural Studies, 2021)
We are living in unprecedented times of migration flows. There are over 271.6 million international migrants globally, most of them women and children under the age of 19, most of whom move to cities causing fast growth in urban areas, particularly in the informal settlements and slums, places of poverty, densely populated with inadequate household water and sanitation, little or no waste management, overcrowded public transport and limited access to formal health care facilities. As they seek to establish themselves in the city, many migrants turn to religion for support. Faith communities become places where they can find 1) a source of community; 2) where resources are available to meet their needs; 3) for support in times of trouble; and 4) where praying becomes a resource for survival. As the Covid-19 pandemic began spreading throughout the world and cities were locked down, people were requested to stay in their homes, but yet they had no income or food, causing hunger, anxiety, fear and violence. But once again faith communities, already on the ground, have responded, and from these responses are lessons to be learned on how to support bottom-up approaches that build resiliency and strengthen informal communities in times of crisis. 5 principal ways that religious communities are helping to build resilient cities: data collection, developing partnerships and networks, providing information and communication, inclusive and diverse engagement, and spiritual comfort and guidance. These types of responses create resilient communities than can withstand future pandemics.